Motivation in Improving Work Discipline - Hafizah, Casyariadi Vana; Hayati, Fitri (Indikator Pendidikan Indonesia, 2022)
The research aims to identify and analyze the role of motivation in improving work dicipline. In this study, the Litarature Study Research Method was applied, namely the data collection technique by conducting a review study of books, literarure, notes, and reports that had something to do with the problem being solved. With the support of several other research samples, it can be proven that motivation can have an affect on increasing work discipline. And work discipline affects employee performance. To achieve company goals, managing human resources has the potential to affect employye performance and affect company performance.